Entrepreneurship, Economic Mobility, and Entrepreneurial Propensity: A Regional View Based on the Analysis of Selected Latin American Countries - Hugo D. Kantis; Juan S. Federico; Luis A. Trajtenberg (Inter-American Development Bank (IDB), 2012)
Using household surveys from Argentina, Brazil, Peru, Ecuador, and El Salvador, this paper assesses the contribution of entrepreneurship to socioeconomic mobility and to understand the main variables associated with entrepreneurial propensity in selected Latin American countries. It is found that, at the aggregate regional level, income mobility is rather modest and that entrepreneurs do not outperform the rest of the population. However, entrepreneurs tend to perform as well as or better than non-entrepreneurs in countries where relative income mobility is moderate. In countries where relative income mobility is rather low, entrepreneurs tend to show less income mobility. Entrepreneurial propensity is rather modest, at 10 percent of the population. University graduates show the highest propensity in most of the countries studied, while women and young people were found to have the lowest entrepreneurial propensity.
Keywords: L26; 330